DUSP1 Is a Potential Marker of Chronic Inflammation in Arabs with Cardiovascular Diseases - Khadir, Abdelkrim; Kavalakatt, Sina; Dehbi, Mohammed; Alarouj, Monira; Bennakhi, Abdullah; Tiss, Ali; Elkum, Naser (Disease Markers, 2018)
Background. Cardiovascular disease (CVD) risks persist in patients despite the use of conventional treatments. This might be due to chronic inflammation as reflected in epidemiological studies associating circulating low-grade inflammatory markers with CVD recurrent events. Here, we explored this potential link by assessing plasma dual-specificity phosphatase 1 (DUSP1) levels and comparing them to high-sensitivity CRP (hsCRP) and oxidized low-density lipoprotein (oxLDL) levels and their associations to conventional CVD risk factors in confirmed CVD patients. Methods. Human adults with reported CVD (n=207) and controls (n=70) living in Kuwait were used in this study. Anthropometric and classical biochemical parameters were determined. Plasma levels of DUSP1, oxLDL, and hsCRP were measured using human enzyme-linked immunosorbent assay kits. Results. DUSP1 and hsCRP plasma levels and their least square means were higher in CVD cases, while oxLDL plasma levels were lower (p<0.05). Multivariate logistic regression analysis showed that DUSP1 and hsCRP are independently associated with CVD in the studied population, as reflected by 2-fold and 1.5-fold increased risks with increased levels of DUSP1 and hsCRP, respectively. In our study, DUSP1 levels were found to be associated with CVD despite statin treatment and diabetes status (p<0.05), whereas hsCRP mainly correlated with obesity markers. Conclusions. Circulating DUSP1 might be a predictor of chronic subclinical inflammation and residual risk in CVD patients, whereas our data suggest that the association between hsCRP and CVD is largely accounted for adiposity risk factors.